الشيخ محمد تقي العثماني : " منهجة وافكاره في شرح أحاديث المعاملات المالية في كتابه " تكملة فتح الملهم بشرح صحيح الامام مسلم - Zunaidah Mohd Marzuki (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
This research treats an important topic of Hadith exegesis concerning the methodology and ideas of Sheikh Muhammad Taqi Al-Uthmani in commenting Hadith on financial transactions in his book “Complement of FatÍ al-Mulhim bi Sharh Sahih al-Imam Muslim”. The research contains the biography of Sheikh Muhammad Taqi Al-Uthmani, his scholarly positions, the features and the importance of his book, Al-Takmilah, the general writing methodology of the author, his peculiar method and ideas in explaining the Hadith on financial transactions, and his stand with regard to some of the contemporary issues of financial transactions. This research relies on descriptive method in presenting information regarding the life of the author and his book, Al-Takmilah as well as his general methodology of writing, while adopting inductive method in collecting and selecting materials concerning the Hadith on financial transactions from books, journals and other periodical materials. Analytical method was used in explaining his methodology and ideas in commenting on the Hadith on financial transactions of Sahih Muslim. To a lesser extent, this research also utilized comparative methodology, personal interview and correspondence. Finally, the research reaches several results which specifically show that this commentary is still considered as in the realm of the early scholars' commentaries presented in modern styles in terms of language, Hadith sciences and juristic points of views. This study also points out that this commentary is influenced by Hanafi's jurisprudence points of view though tolerating and outweighing other schools of jurisprudence on several issues. Another important finding is that this commentary also treats some significant contemporary issues like abstract rights (Al-Huquq al Mujarradah) and marketable securities (Al-Awraq Al-Maliyyah). It also refutes some contemporary misconceptions like the issue of land ownership (Milkiyyah Al-Ard) and the issue of interest (Al-Riba). One of the important recommendations outlined by this study is the importance of further study of the author's other books relating to the Hadiths on financial transactions. Due to the specialist background of the author in Islamic jurisprudence, it is also recommended to study other issues in this very commentary, especially on the jurisprudence of legal issues (Qadaya Al-Ahkam au Al-Huquq Al-Qanuniyah).